Building Tradition, Slum and Housing the Urban Poor: An Exploratory- Study (2016)
In most developing countries today, the provision of housing is grossly inadequate, coupled with the fact that the available housing falls below the standard of appropriate habitable models. This is so despite decades of direct government intervention in the housing sector. It is estimated that more than 50 percent of the urban population in the developing countries lives at the level of extreme poverty. The adoption by the United Nations General Assembly of the Global Strategy for Shelter to the Year 2000 (GSS) in 1988 implied a global recognition of the severity of the housing problem in the developing and underdeveloped countries. There is the need to address these gross inadequacies in terms of quantity and quality of housing provided. According to the Nigeria population census figures of 2006, Nigeria has over 140 million people (currently estimated to be 173.6 million in 2015); placing it as the most populous country in Africa, Many of this population are found living in the major urban centres, with over 70 per cent classified as living under poor and inadequate condition of housing. The paper, using case study approach, explores the issues surrounding the provision of adequate housing in a millennium city of Akure, Nigeria. It made use of data and information collected from both primary and secondary sources. Data were collected through physical investigation of poor inner- city neighbourhoods of the study area; stating some of the findings as framework for the design of future developmental policy. In conclusion, the paper argues for a rethink of policies and increase in investment in the built environment to positively alleviate the adverse housing condition.